Diabetes mellitus; its impact on periodontal health and dental caries - Ramli, Nur Izzati Najwa; Syed Mohamad Nadzir Alkaff, Syarifah Nur Izzati Alkaff; Faisal, Ghasak Ghazi; Al-Bayati, Lena Hilal Aboud (2016)
To study the relationship between diabetes mellitus, periodontal health status and dental caries. A case-control study involving 42 diabetic patients and 42 non-diabetic patients was conducted at the dental clinic, Kulliyyah of Dentistry, International Islamic University Malaysia. Full mouth periodontal examination was performed and their decay, missing, filling, total score (DMFT) was obtained. The percentage of diabetic patients that were diagnosed with periodontitis was 88.1% compared to 59.5% in the control group and it was statistically significant (p<0.05). In comparing periodontitis in both groups, the bleeding on probing (BOP) and pocket depth (PD) showed no significant difference (p>0.05) while the clinical attachment loss (CAL) showed significant difference (p<0.05). The mean values for decay, missing and filled teeth in the diabetic group were 2.24±1.94, 8.52 ±6.13and 3.76± 2.79 respectively. Meanwhile, in the control group the mean values were 1.83±1.92, 4.79±3.80and 2.79 ±2.76 respectively. Among all three mean values, missing teeth was the only one that showed significant difference (p<0.05) However, the total DMFT score between the two groups showed statistically significant result (p<0.05). Diabetic patients are more prone to periodontal destruction and tooth loss and they may also be at a higher risk of developing dental caries. Regular dental follow up are required for diabetic patients.